Algorithm for converting 3D objects into rolls using spiral coordinate system. Issue 2 (2nd April 2016) - Shulunov, Vyacheslav R.
ABSTRACT: The article reports about the algorithm of converting objects into a flat ribbon in the process of roll powder sintering (RPS) additive manufacturing technology. The main idea of the author is to conform the transformation of spiral of Archimedes to 3D space. This algorithm is based on linear rolling effect. It is well known that any plane can be transformed into a roll and, in this way, the third dimension appears. Thus, two-dimensional space and height provide the conformity between ( x, y, z ) and ( l, z ) coordinates. This work describes how the algorithm of precise transformation of a 3D object to a flat ribbon, using the spiral coordinate system, has been designed and implemented with a varied layer thickness, a winding axle and resolution. The algorithm has been extensively tested with the help of several parts of computer aided design models based on the RPS process.